Deliberação e problematização socioambiental em torno da PCH Aiuruoca: a constituição política da categoria de atingidos - Hellen Salgado Guicheney e Almeida Castro (2008)
In this text, the deliberative process is understood as a conflicting crosspoint of discursive exchanges originated in different communicative contexts. Based on that, an empirical study was conducted on a socio-environmental conflict, trying to understand how the themes and the changes of points of view happen. We investigate how the residents of Aiuruoca, a city in the south of the state of Minas Gerais, build, negotiate, and dispute what it means to be "damaffected"by the construction of the Small Hydroelectric Power Plant (PCH) in the municipal district. The Previous License of PCH-Aiuruoca was awarded in spite of the irregularities that occurred on that stage of the environmental licensing, as well as in spite of state and federal lawsthat were supposed to guarantee the protection of that region which is an important preservation area of the Mata Atlantica biome. Our analysis centers its attention on the Public Hearing that took place in 2002, in the context of the judgment of the enterprises License. The hearing has anadvisory goal, and it is a formal, and necessary stage of the licensing process. It gathered many social actors involved in the subject, such as the entrepreneur, the responsible environmental organs, members of the local associations, some residents, and the dam-affected groupconsultantship. We show that there exists serious discussion restrictions imposed by these contexts. They are related mainly to what can or cannot be said, to who participates, and to what kind of arguments can be pointed out. In our opinion such restrictions are similar to the generalcritics of other participation spaces, and they do not invalidate the importance of the wider deliberative process. We reveal how the hearings can promote opportunities to make explicit the conflicts main arguments. In our view, they help the participants to interpret different dimensions of the public problems that concerned them and to discover deficiencies, difficulties, and progresses in the building of a wider understanding. Focusing on how the people talk about the suffered damages, how the generalization of the arguments occurs and on the constitution ofdiscursive collisions, we reveal the way by which the category of being a dam-affected is constructed.